Hypomethylation associated vitamin D receptor expression in ATP1A1 mutant aldosterone-producing adenoma. (15th May 2022) - Nanao, Yuta; Oki, Kenji; Kobuke, Kazuhiro; Itcho, Kiyotaka; Baba, Ryuta; Kodama, Takaya; Otagaki, Yu; Okada, Akira; Yoshii, Yoko; Nagano, Gaku; Ohno, Haruya; Arihiro, Koji; et al.
Abstract: DNA methylation alteration is tissue-specific and play a pivotal role in regulating gene transcription during cell proliferation and survival. We aimed to detect genes regulated by DNA methylation, and then investigated whether the gene influenced cell proliferation or survival in adrenal cells. DNA methylation and qPCR analyses were performed in nonfunctioning adrenocortical adenoma (NFA, n  = 12) and aldosterone-producing adenoma (APA, n  = 35) samples. The VDR gene promoter was markedly hypomethylated in APA with ATP1A1 mutation, and the promoter methylation levels showed a significant inverse association with the transcripts in APA. ATP1A1 mutation led to VDR transcription in HAC15 cells, and VDR suppression abrogated ATP1A1 mutation-mediated cell proliferation in HAC15 cells. We demonstrated that APA with ATP1A1 mutation showed entire hypomethylation in the VDR promoter and abundant VDR mRNA and protein expression. VDR suppression abrogated ATP1A1 mutation-mediated cell proliferation in HAC15 cells. Abundant VDR expression would be essential for ATP1A1 mutation-mediated cell proliferation. Graphical abstract: Image 1 Highlights: VDR gene promoter was hypomethylated especially in APA with ATP1A1 mutation. APAs with ATP1A1 mutation had abundant VDR mRNA and protein expression. ATP1A1 mutation led to VDR transcription in HAC15 cells. VDR suppression inhibited ATP1A1 mutation-mediated cell proliferation in HAC15 cells.